Comités de Tierra Urbana (CTUs) and the 'Right to the city': urban transformations in Venezuela's Bolivarian revolution - Martinez, Jennifer Lynette (2012)
The Venezuelan Bolivarian Revolution has provoked researchers to find new ways of engaging with the emergence of popular organizations and movements who are highly mobilized and seeking new forms of popular power and the deepening of democratic practices both within the country and for the Latin American region. This research project argues that at the core of the Bolivarian Revolution is an urban revolution in which barrio residents play a key role in the transformation of the country. Drawing on the work of Henri Lefebvre, David Harvey, Neil Smith, Doreen Massey, and Edward Soja, among others, it is argued that a spatial analysis of urban social relations, while usually reserved for the study of capital’s role in producing contemporary cities, also allows research to visibilize how popular organizations act as agents in the production and transformation of urban space in their own right.